Antimicrobial activity of fibrinogen and fibrinogen-derived peptides – a novel link between coagulation and innate immunity - Påhlman, Lisa I.; Mörgelin, Matthias; Kasetty, Gopinath; Olin, Anders I.; Schmidtchen, Artur; Herwald, Heiko (Thrombosis and Haemostasis, 2013)
Fibrinogen is a key player in the blood coagulation system, and is upon activation with thrombin converted into fibrin that subsequently forms a fibrin clot. In the present study, we investigated the role of fibrinogen in the early innate immune response. Here we show that the viability of fibrinogen-binding bacteria is affected in human plasma activated with thrombin. Moreover, we found that the peptide fragment GHR28 released from the p-chain of fibrinogen has antimicrobial activity against bacteria that bind fibrinogen to their surface, whereas non-binding strains are unaffected. Notably, bacterial killing was detected in Group A Streptococcus bacteria entrapped in a fibrin clot, suggesting that fibrinogen and coagulation is involved in the early innate immune system to quickly wall off and neutralise invading pathogens.
Keywords: Innate immunity; coagulation; fibrinogen; infection